LIVED ONTOLOGIES: CICERO, AGAMBEN, AND THE PHILOSOPHY OF LIFE. - von Eggers, Nicolai (Symposium: Canadian Journal of Continental Philosophy / Revue Canadienne de Philosophie Continentale)
In this article, I analyze the relation between ontology and practical philosophy in Cicero's work and the role Hellenistic philosophy plays within the work of Giorgio Agamben. I discuss the relation between life and ontology, between philosophy as a guide to living and philosophy as the study of being. Unlike philosophers who treat Hellenistic philosophy as a form of therapy (Nussbaum, Foucault, Hadot), I show how Agamben interprets Hellenistic philosophy as oppressive by turning the theory of being into an injunction of having-to-be. For Agamben, every philosophy implies a certain form of life, and it is thus impossible to distinguish between ontology and living. The aim of philosophy, therefore, is not to be therapeutic but rather to develop an ontology that will allow for humanity to live without oppression. Through a detailed reading of Cicero's concept of "nature," I develop the reading and critique of Cicero suggested by Agamben.